CONTENT ANALYSIS OF CHILDREN LITERATURE (POETRY) IN THE 2013 CURRICULUM ELEMENTARY SCHOOL STUDENT BOOK IN SHAPING CHILDREN'S PERSONALITY CHARACTERISTICS: AN OVERVIEW OF STYLISTIC ANALYSIS - Dirneti; Tisrin Maulina Dewi; Edi Kurniawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Literary work is the result of an author's imagination expressed through the medium of language. One form of literary work is poetry. As a literary work, poetry is bound by lines and stanzas. This study discusses the content of children's literature (poetry) contained in the 2013 curriculum thematic books of elementary school and how these poems shape students’ personality characteristics based on stylistic analysis. The purpose of the study was to determine the stylistic elements of children's poetry found in the thematic books used in elementary schools under the 2013 curriculum. This research employed a qualitative approach using a descriptive method. The study was conducted in the form of documentation analysis, examining the poems presented in the elementary school thematic books; thus, the objects of the research were the forms of poetry themselves. Based on the results of data analysis, it was found that the children’s poetry contained in the books utilized several sound elements, such as rhyme, alliteration, assonance, anaphora, epanalepsis, mesodiplosis, and onomatopoeia. The use of diction found in the book included Arabic diction. The imagery used consisted of visual, auditory, olfactory, and gustatory images. The figures of speech employed in the poems included personification, hyperbole, metaphor, and simile. Furthermore, several forms of language deviation were identified, such as morphological, syntactic, and graphological deviations. The forms of children’s poetry in the thematic books were designed in accordance with the characteristics of children's poetry, as reflected in the use of sound elements, diction, figures of speech, imagery, and language deviations.